PENGELOLAAN KANTIN SEKOLAH SEHAT DALAM MENINGKATKAN KEBERSIHAN DAN KENYAMANAN LINGKUNGAN PADA MADRASAH ALIYAH NEGERI 1 MERANGIN - Ahmad Khoiron Abdan Sakur; M. Syahran Jailani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the management of healthy school canteens in improving environmental cleanliness and student comfort at MAN 1 Merangin. The study employs a qualitative descriptive method with a naturalistic inquiry approach. Data were collected through in-depth observations, documentation, and interviews with the Vice Head of Madrasah, the Chairperson of the Canteen Committee, teachers, and students. The results indicate that the management process is carried out through an integrated system, starting from selective planning and standardizing nutritional and halal quality to a formal organizational structure. Implementation is realized through disciplined daily sanitation routines, a centralized waste management system, and collaborative supervision with the local Health Center (Puskesmas). Despite facing challenges such as a reduction in management personnel and economic shifts, the madrasah has implemented strategic efforts through humanist fee reduction policies and consistent character building for students. The study concludes that effective canteen management serves as a primary pillar in creating a healthy, clean, and psychologically comfortable educational ecosystem, which supports the overall quality of student life and learning at MAN 1 Merangin